Insights from post-test examination of three packages from the MiniCan test series of copper-cast iron canisters for geological disposal of spent nuclear fuel: impact of the presence and density of bentonite clay. (28th April 2017) - Johansson, Adam Johannes; Lilja, Christina; Sjögren, Lena; Gordon, Andrew; Hallbeck, Lotta; Johansson, Linda
ABSTRACT: MiniCan is a field test designed to highlight certain aspects of corrosion in a KBS-3 type repository for spent nuclear fuel. Five experimental packages containing miniature copper-cast iron canisters were installed in the Äspö Hard Rock Laboratory in 2006. Three packages have been retrieved, MiniCan 3 in 2011 and MiniCan 4 and 5 in 2015. The packages were examined regarding surface chemistry, microbiology and corrosion of copper and iron. The main difference in design between the retrieved packages was the presence and density of bentonite clay. Black deposits of sulphides were visually noted during dismantling of both MiniCan 3 (low density clay) and MiniCan 5 (no clay), but not in MiniCan 4 (high density clay). Extensive corrosion of cast iron specimens was observed in all three packages, with local attacks corresponding to the loss of hundreds of µm/y. Sulphate reducing bacteria (SRB) were found to be present in ground water, in bentonite clay and on surfaces of various specimens of iron and copper, and it is suggested that the SRB activity had a pronounced influence on the corrosion observed. Copper surfaces display a roughness at the µm level and the integrated corrosion rate of copper mass-loss specimens was generally low. This paper is part of a supplement on the 6th International Workshop on Long-Term Prediction of Corrosion Damage in Nuclear Waste Systems .